Demands of experiential training for ICU nurses in Hunan of China - Xie, Yijia (Int J Nurs Sci, 2020)
OBJECTIVE: To assess intensive care unit (ICU) nurses’ demands for specialized experiential training and to provide inputs for developing an experiential training program for ICU nurses. METHODS: A questionnaire for assessing ICU nurses’ demands for experiential specialty training was distributed to 360 ICU nurses, selected through purposive sampling from two secondary hospitals and six tertiary hospitals in Hunan Province, China. RESULTS: Of the survey participants, 63.6% had undergone a specialty training program for ICU nurses. Of these individuals, 53.0% were satisfied with the training. Certification as a qualified nurse was considered an essential criterion for admission of trainees into the program by 81.8% of respondents, while 77.1% of respondents considered clinical working experience to be a critical requirement for selecting trainers. A total of 48.1% of the respondents preferred part-time training, and 36.1% considered a training cycle of 9–12 weeks to be reasonable. Moreover, they felt that the training methods should be tailored to different stages of the experiential learning cycle. Demands for experiential training among ICU nurses were quantified, with high demand reflected in an overall score of 4.41 ± 0.48. The “intensive care technology” experiential training module was ranked highest in terms of demand, with the top five sub-modules being specialty operating technology (4.67 ± 0.53), care of critically ill patients (4.66 ± 0.55), critical patient rescue procedures (4.65 ± 0.56), assessing monitoring indexes (4.63 ± 0.56), and the application of relevant instruments (4.61 ± 0.57). CONCLUSION: Nearly half of the respondents indicated that their experiences of specialty training programs were not satisfactory, and they had high demands for experiential training. Thus, to optimize training outcomes, continuous updating of training methods is essential. Moreover, a systematic, comprehensive, and multilevel experiential training program that targets the specific needs of ICU nurses is essential.